Students’ Satisfaction with Accounting Teachers’ Lesson Delivery, the Role of Perceived Quality of Lesson Delivery in Ghanaian Senior High Schools - Debrah, Ofori; Inusah, Nasiru; Dwommor, Joseph Yaw (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">To highlight the importance of the quality of lesson delivery for students’ satisfaction with the teaching and learning process in the classroom, this study examines the quality factors of accounting teachers lesson delivery that may influence students’ satisfaction with accounting teachers’ lesson delivery in Senior High Schools in Ghana. Survey questionnaire, a modified version of SERQUAL model, was used in collecting data for this study. In all, a sample of 504 students from 20 public Senior High Schools in Kumasi metropolis in the Ashanti region of Ghana participated in the survey. The findings of this paper suggest that accounting students in Ghanaian Senior High Schools are generally not satisfied with the quality of lesson delivery of their financial accounting teachers. In addition, classroom setting (environment, facilities and materials) and teachers’ teaching behavior (responsive to students’ needs, reliability, competency, and empathy) do not meet Senior High School accounting students’ expectations. It is evident from the results that teachers’ performance in lesson delivery, as perceived by students, influence students’ satisfaction with lesson delivery in the classroom. Perceived low performance on the service quality dimensions of accounting teachers’ lesson delivery seems more susceptible to low satisfaction with teachers’ lesson delivery. These findings imply that, quality of accounting teachers’ lesson delivery, especially, along the dimensions of tangibility, responsiveness, reliability, assurance and empathy in their lesson delivery requires improvement. There is the need for teachers and school managers to identify what students really expect from teachers in their lesson delivery so that teachers can make the necessary changes to improve lesson delivery quality and students’ satisfaction in the classroom.